AB1849 AUTOIMMUNE MANIFESTATIONS OF CTLA-4 HAPLOINSUFFICIENCY IN TWO PATIENTS OF SOUTHEAST ASIAN ETHNICITY - Lai, Y. W.; Tan, J.; Thong, B. Y. H.; Lim, Y. L.; Lee, J.; Chua, C. G.; Lim, X. R. (Annals of the rheumatic diseases, 2023)
BackgroundCytotoxic T- lymphocyte antigen 4 haploinsufficiency (CTLA4-H) is an autosomal dominant monogenetic disorder caused by heterozygous CTLA4 germline mutation.[1] Its diagnosis is complicated by a highly variable clinical phenotype including an immune dysregulation syndrome with autoimmunity, lymphoproliferation, atopy and malignancy; as well as immunodeficiency with hypogammaglobulinemia and recurrent infections.[2] CTLA4-H has been reported mainly in North America and Western Europe, whilst lipopolysaccharide-responsive beige-like anchor (LRBA) deficiency (LATAIE) mainly in East Asia.[3]ObjectivesTo raise awareness of adults with CTLA4-H presenting with varied autoimmune end-organ manifestations to rheumatologists.MethodsCase reports.ResultsA 53-year-old Malay male first developed violaceous papules and nodules on both legs and arms at the age of 44 years old. He later developed widespread lymphadenopathy, maxillary sinusitis, lung nodules, cholestatic hepatitis, splenomegaly and thrombocytopenia over the course of the next 6 years. Biopsy of the skin, lymph nodes and liver all demonstrated non necrotizing granulomas and returned negative for mycobacterial studies and malignancy. He was diagnosed with sarcoidosis and started on moderate dose corticosteroids and azathioprine. He later developed hypogammaglobulinemia, listeria meningoencephalitis and two episodes of disseminated zoster, prompting further evaluation. Genetic analysis identified a missense variant of uncertain significance (VUS) c.506C>A (p.Ala169Glu) in the CTLA-4 gene. Functional testing showed reduced expression of CTLA-4 on both unstimulated and stimulated Foxp3+T cells by flowcytometry. He is treated with regular replacement intravenous immunoglobulin (IVIg), prednisolone and ciclosporin.The second patient is a 28-year-old Chinese male with a prior history of endogenous eczema diagnosed at 13 years old. He developed recurrent sinusitis at 18 years old, followed by 3 episodes of pneumonia over a course of 2 years. He was found to have chronic rhinosinusitis, bronchiectasis, hypogammaglobulinemia, blunted post-vaccination responses to pneumococcus and tetanus. He was initially treated for Common Variable Immunodeficiency with regular IVIg while continuing to require regular prednisolone for control of eczema. 2 years later, he developed immune-mediated thrombocytopenia. He later developed photosensitive eczematous patches over his face, chest, legs and the diagnosis was revised to chronic actinic dermatitis. He was eventually found to have a novel deletion on his CTLA4 gene c.522del (p.Leu174Phefs*13) on genetic analysis, reduced CTLA4 expression on resting Treg cells by flowcytometry, with levels returning to normal with stimulation. He is treated with regular IVIg, prednisolone and methotrexate.ConclusionDiagnosis of adult-onset primary immunodeficiency syndromes can be a challenge when these present with autoimmune phenomena rather than recurrent infections. Genetic testing in this era of rapidly expanding knowledge of inborn errors of immunity and detection of VUS may have potential clinical and therapeutic implications.References[1] Mitsuiki N, Schwab C, Grimbacher B. What did we learn from CTLA-4 insufficiency on the human immune system? Immunol Rev. 2019;287(1):33-49.[2] Schwab C, Gabrysch A, Olbrich P, Patino V, Warnatz K, Wolff D, et al. Phenotype, penetrance, and treatment of 133 cytotoxic T-lymphocyte antigen 4-insufficient subjects. J Allergy Clin Immunol. 2018;142(6):1932-46.[3] Jamee M, Hosseinzadeh S, Sharifinejad N, Zaki-Dizaji M, Matloubi M, Hasani M, et al. Comprehensive comparison between 222 CTLA-4 haploinsufficiency and 212 LRBA deficiency patients: a systematic review. Clin Exp Immunol. 2021;205(1):28-43.Acknowledgements:NIL.Disclosure of InterestsNone Declared.